(untitled) (Fiep Bulletin - online, 2014)
This study seeks to understand the reality of public school teachers of middle level technical, more specifically the nursing technical course in the years 2012 and 2013. The collection happened by means of questionnaires. The study was approved by the Research Ethics Committee of the Universidade Estadual do Oeste do Paraná under opinion No. 13312011. As for the profile of professors of nursing technician, 14 teachers responded to the questionnaire, these 12 (86) are female and 2 (14) male, and 5 (36) had age between 20 and 30 years, 6 (43) between 31 and 40 years, 1 (7) between 41 and 50 years, 1 (7) above 50 years and 1 (7) didn’t answer the question. The case of the 14 ’s education teachers have a degree in nursing in the undergraduate and Bachelor, 1 (7) professor, besides this training, has a degree in pedagogy. When the graduate, 11 (79) possess expertise, 1 (7) master and 2 (14) do not have graduate degrees. With respect to time of performance in teaching, 4 (29) working in the area with less than 3 years, 7 (50) Act with time between 3 and 6 years old, 2 (14) Act for 10 years and 1 (7) operates to 20 years. Thus, 11 (79) teachers have worked also in nursing care and 3 (21) only worked on teaching. It is believed that this study has contributed to better understand who are the teachers and what their socioeconomic conditions, since the levels of teachers ’ quality of life can affect directly their concerns and professional satisfaction, which can influence the quality of education.